2013
DOI: 10.2495/eres130031
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake recurrence and seismic hazard assessment: a comparative analysis over the Italian territory

Abstract: Rigorous and objective testing of seismic hazard assessments against real seismic activity are a necessary precondition for any responsible seismic risk assessment. The reference hazard maps for the Italian seismic code, obtained with the classical probabilistic approach (PSHA) and the alternative ground shaking maps based on the neo-deterministic approach (NDSHA) are crosscompared and tested against the real seismicity for the territory of Italy. NDSHA is a methodology that allows for the sound definition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Giardini et al 2003) is not reliable for many reasons well described in recent literature, and these statistical approaches should be validated by means of physical approaches like NDSHA for the sake of safety. (3) For a detailed comparison of PSHA and NDSHA performances, see Peresan et al (2013), who, comparing the standard NDSHA map and the maps of ground motion for a given return period in the Italian region, concluded that the introduction of a return period causes a systematic underestimation of the expected ground motion. When the reference hazard maps for the Italian seismic code, obtained by PSHA, and the ground motion maps, based on NDSHA, are tested against the real seismicity for the territory of Italy, the comparison shows that, as a rule, the predictions provide rather conservative estimates and that the NDSHA maps appear to outscore the PSHA Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Giardini et al 2003) is not reliable for many reasons well described in recent literature, and these statistical approaches should be validated by means of physical approaches like NDSHA for the sake of safety. (3) For a detailed comparison of PSHA and NDSHA performances, see Peresan et al (2013), who, comparing the standard NDSHA map and the maps of ground motion for a given return period in the Italian region, concluded that the introduction of a return period causes a systematic underestimation of the expected ground motion. When the reference hazard maps for the Italian seismic code, obtained by PSHA, and the ground motion maps, based on NDSHA, are tested against the real seismicity for the territory of Italy, the comparison shows that, as a rule, the predictions provide rather conservative estimates and that the NDSHA maps appear to outscore the PSHA Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NDSHA permits (if really necessary, as claimed by PSHA addicted practitioners fearful of "overdesign" because a damaging earthquake is unlikely) an accounting for earthquake occurrence rate (Peresan et al, 2013;Nekrasova et al, 2013;Magrin et al, 2017; and references therein): first, the characterization of the Frequency-Magnitude (FM) relation for earthquake activity in Italy is performed, according to the "multi-scale seismicity model" (Molchan et al, 1997), such that a robust estimated occurrence (not recurrence) rate is associated to each of the NDSHA modeled sources; and second, the occurrence rate assigned to the source is thus associated to its pertinent synthetic seismogram, coherently with the physical nature of the problem. Accordingly, then, two separate maps are obtained: (1) one for the "ground shaking" and (2) another for the corresponding perceived "average occurrence rate", as shown in Fig.…”
Section: Ndsha Grid Cells: a Honeycomb Of Seismic Sources | Computed Seismogramsmentioning
confidence: 99%
“…In addition, NDSHA permits (if really necessary, as claimed by PSHA addicted practitioners fearful of "overdesign" because a damaging earthquake is unlikely) an accounting for earthquake occurrence rate (Peresan et al, 2013;Nekrasova et al, 2013;Magrin et al, 2017; and references therein): first, the characterization of the Frequency-Magnitude (FM) relation for earthquake activity in Italy is performed, according to the "multi-scale seismicity model" (Molchan et al, 1997), such that a robust estimated occurrence (not recurrence) rate is associated to each of the NDSHA modeled sources; and second, the occurrence rate assigned to the source is thus associated to its pertinent synthetic seismogram, coherently with the physical nature of the problem. Accordingly, then, two separate maps are obtained: (1) one for the "ground shaking" and (2) another for the corresponding perceived "average occurrence rate", as shown in Fig.…”
Section: Ndsha Grid Cells: a Honeycomb Of Seismic Sources | Computed Seismogramsmentioning
confidence: 99%